The role of species of carex l. Genus in the vegetation of the relict lake Kravtsovo (Stavropol plateau) - Valentina Valentinovna Volkova; Natalya Gennadievna Likhovid (Наука. Инновации. Технологии, 2022)
When analyzing literary data and herbarium funds, we found that 14 species of sedges grew in the coastal zone of the lake. When conducting a survey of the coastal zone of the lake, we found a decrease in the number of species of the genus. Within 2011-2017 we have not identified C. vesicaria L., C. secalina Wahlenb., C. elata All., C. paniculata L., C. disticha Huds., C. divisa Huds on the above mentioned territories. The state of populations of C. vulpina, C. pseudocyperus, C. diluta, C. acutiformis, C. melanostachya, C. riparia, C. lasiocarpa, C. hirta, C. acuta remained almost the same. A certain decrease in C. lasiocarpa, C. pseudocyperus, C. diluta population area has been determined.